ChemInform Abstract: Electrochemical Li+ Insertion Capabilities of Na4‐xCo3 (PO4)2P2O7 and Its Application to Novel Hybrid‐Ion Batteries. Issue 30 (29th July 2014) - Nose, Masafumi; Nobuhara, Kunihiro; Shiotani, Shinya; Nakayama, Hideki; Nakanishi, Shinji; Iba, Hideki
Abstract Electrochemical oxidation of Na4Co3 (PO4)2P2O7 yields Na‐deficient Na4‐xCo3 (PO4)2P2O7 with both Li+ and Na+ insertion capabilities as a hybrid‐ion electrode material.